Solar photovoltaic/thermal air collector with mirrors for optimal tilts - Assia Benkaddour; Hanan Boulaich; Elhassan Aroudam (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This work is the result of a study of a photovoltaic/thermal air collector that concentrates solar radiation using two mobile mirrors to enhance electrical and thermal energy. The study is made for the site of Tetouan (Morocco) (longitude=-5°, latitude=35.25°) for a daily variation during typical days in May, June, September, and December, days considered as clear sky. To prove the effectiveness of the mirrors on the production of both electrical and thermal energy by the collector, we compared their electrical and thermal efficiency in two cases, without and with mirrors at the optimal positions. We validate the obtained simulation results by comparing them to the results from experimental studies published in the literature, for which a strong agreement was obtained. The model estimates the solar energy received by the hybrid collector during the day, to optimize the performance of the fixed collector, we have searched for the values of the optimal daily tilt angles of the two mirrors which allowed us to enhance the quantity of incoming solar radiation on the collector. The tilt angles depend on the sun’s elevation angle, the azimuth angle for typical days of the year.